Can liberalised electricity markets deliver on climate change and energy poverty? Evidence from community projects in Great Britain. Issue 9 (2nd September 2022) - Nolden, Colin; Towers, Lee; Schamroth Rossade, Daniela; Thomas, Peter; Speciale, Giovanna; Watson, Richard
ABSTRACT: This paper reports on tensions between decarbonisation and energy poverty priorities in Great Britain's liberalised electricity markets. Switching electricity suppliers in this market can result in significant benefits for those on bad deals. Further benefits are determined by the regulator. However, many of the energy poor lack the capabilities to switch and access these benefits. Community organisations play an important role in providing such access through remedial action. Using the capabilities approach, this paper combines quantitative and qualitative organisational data analysis at a community level to reveal an increasing share of the population who could benefit from switching and who agree to switching. At the same time, eligibility for one-off discounts on electricity bills to support the energy poor has increased sharply in recent years. This data points towards climate mitigation policies and market structures which benefit wealthier groups at the expense of more deprived groups who lack capabilities. At the micro scale, data access and intermediation at various levels and scales can help support more targeted interventions that facilitate well-being and enhanced capabilities. At the macro level, liberalised retail electricity markets need to be accommodated by safety nets and supportive institutional arrangements to avoid competitive pressures translating into complexity and opacity for consumers. Failure to equitably address capability conflicts, also framed as energy justice tensions and trade-offs, risks reinforcing and creating new injustices.